2023
DOI: 10.3390/su15097235
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Augmented Reality in Language Learning

Abstract: As an emerging technology, augmented reality has been increasingly entering the educational field. Previous studies of AR are strongly associated with scientific education but lack the mention of language learning. This study aimed to analyze the use of AR tools in language learning contexts using the bibliometric tools VOSviewer and CitNetExplorer using both qualitative and quantitative research methods. This study analyzed the top ten authors, sources, countries, and organizations using VOSviewer and establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Language learning is another area where AR has shown significant potential. Min and Yu (2023) conducted a bibliometric analysis of AR in language learning, revealing that both teachers and students have a positive attitude towards AR tools in this context. The study found that AR tools enhance language learning by providing an immersive learning context, increasing motivation, facilitating interaction, and reducing anxiety.…”
Section: Literature Review Understanding Ar/vr In Educational Contextsmentioning
confidence: 99%
“…Language learning is another area where AR has shown significant potential. Min and Yu (2023) conducted a bibliometric analysis of AR in language learning, revealing that both teachers and students have a positive attitude towards AR tools in this context. The study found that AR tools enhance language learning by providing an immersive learning context, increasing motivation, facilitating interaction, and reducing anxiety.…”
Section: Literature Review Understanding Ar/vr In Educational Contextsmentioning
confidence: 99%
“…These tools, first developed a decade ago, are seeing increased and significant use in publication analysis, in particular for environmental scans and surveys. Visualization has become an important tool across understanding research domains as varied as deep learning in autonomous vehicles [86], understanding how COVID-19 has shaped research [87], and the links with Augmented Reality in learning [88]. This work has chosen VOSViewer for use, but does not preclude the use of other tools for future comparative analysis.…”
Section: Current State Of the Artmentioning
confidence: 99%